Interactive Multimedia to Improve the Students’ Ability of Teacher Training and Education Faculty in Learning Strategy Course - Rita Susila, Heni; Muslim, Suyitno; Syahrial , Zulfiati (International Journal of Psychosocial Rehabilitation, 2020)
Learning strategy is a crucial subject matter for students of teacher and education faculty, they need this course in the order they can choose the right strategy in designing an instructional class. Moreover, they have to pass this course before getting microteaching and practical teaching at school. This study was a research and development (R&D) of interactive multimedia for learning strategy course. The method study refers to the steps of Alessi & Trollip which are conducted through three phases, planning, design, and development. In this learning, students learn the material from the book collaborated by watching interactive multimedia before discussion in the classroom. In the classroom students discuss, solving some problems and doing simulation by lecturer guidance. This learning model was built and validated by professionals and students. Five experts were engaged to assess this model. Experts stated that this model was valid and set to put into practice. To see the effectiveness, pre-test and post-test were performed for students, and the result showed that it can increase learning outcomes. The conclusion is this model was effective in improving students’ achievements in the learning strategy course.